Controlling the output current of a SEPIC H-bridge inverter - Roy Fada Krisna Wisnu Mahendra; Leonardus Heru Pratomo (JURNAL INFOTEL, 2023)
The rapid depletion of fossil fuels and humanity's increasing dependence on electricity drive us to adopt renewable energy-based power generation. However, using renewable energy requires a system to maximize the results of converting renewable energy into electrical energy. An inverter is a DC-to-AC power conversion device. Inverters have two types: buck and boost. In closed-loop control, it can be controlled using current or voltage control. Current-controlled inverters sent to the grid have constraints, such as the inverter input voltage value must exceed the voltage on the grid. This study suggests using an H-bridge inverter and an AC-AC SEPIC to generate a voltage value more significant than the input voltage value. The proposed converter uses a single DC source and bases grid current injection on the regulated output current approach. The proposed converter satisfies the IEEE Std 519-2014 requirement of less than 5% and has a Total Harmonic Distortion (THD) of 4.6%.